Abu ‘Isa al-Warraq’s “Against the Trinity”: A Philosophical Exercise in Comparative Religions - Rashid, Ungaran (2021)
Theological discussions that defend the faith or criticise other religions are common in comparative religion studies. Some Muslim scholars, both in the past and in modern times, such as Ibn Taymiyyah, Al-Biruni, Abu 'Isa al-Warraq, Ahmad Deedat, and Faruqi, express their thoughts on other religions through theological discussions, which are valuable as references in conducting comparative religions and also inter-religious dialogue in the current era. This article discusses the writings of Abu 'Isa al-Warraq in refuting the doctrine of the Trinity. The reason for choosing the book of 'Isa al-Warraq is because his writing entitled Against the Trinity is extraordinary. Al-Warraq’s knowledge of the Trinity doctrine was excellent, unlike most Muslims. Besides, he used his knowledge of the Trinity doctrine to argue that the doctrine was not logical. The use of this logical approach is a good enough approach to do philosophical exercises. This article is primarily based on library research, drawing heavily on Against the Trinity of ‘Isa al-Warraq.